The Reissner - Sagoci Problem for Layered Orthotropic Elastic Media - Rogowski, B. (Engineering Transactions, 1992)
The problem of the torsional displacements of an elastic medium consisting of orthotropic layers, produced by a rigid circular disc attached to the surface is considered. The mixed boundary value problem is reduced to the Fredholm integral equation. The latter is solved by an iterative method, the solution being proved to converge to a unique continuous function.